Energy level determination of purine containing blue light emitting organic compounds - Grzibovskis, Raitis; Vembris, Aivars; Sebris, Armands; Kapilinskis, Zigfrids; Turks, Maris (SPIE - International Society for Optics and Photonics, 2018)
Organic light emitting diodes (OLED) have found their applications in the mobile and TV screens. Till now the commercially available diodes are made by expensive thermal evaporation in a vacuum. The costs of OLED fabrication could be decreased by applying low-cost wet casting methods, for example, spin-coating. In this work, we have studied a group of blue light emitting purine derivatives which could potentially be used in OLEDs. The advantage of these compounds is their ability to form amorphous thin films from solutions. All the thin films were prepared by the spincoating method from chloroform solution on ITO glass. The position of hole and electron transport energy levels is important for efficient OLED fabrication. Ionization energy was determined using photoelectron yield spectroscopy. The gap between ionization energy and electron affinity was determined using photoconductivity measurements. Electron affinity (Ea) then was calculated as a difference between ionization energy (I) and photoconductivity threshold value (Eth). Changes in the energy level values depending on the molecule structure were investigated. The position of electron acceptor group strongly affects the gap between ionization energy and electron affinity, while with the help of the attached substitute groups it is possible to alter the ionization energy. Fine “tuning” of the ionization energy values can be achieved by altering the length of the “tail” where the inactive bulky group is attached.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; OLED; energy levels; photoelectron emission; photoconductivity; purine